Perancangan Sistem Informasi Administrasi dan Pengelolaan Kas Warga Berbasis Web pada Lingkungan RT 005 RW 002 Kelurahan Kedaung - Tegar Andriyansyah; Farizi Ilham; Andra Dwi Okta Ramadhan; Tegar Farhan Maulana (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The administrative and financial management of RT 005 RW 002 Kelurahan Kedaung has been conducted manually using physical cash books. This conventional method creates high administrative burdens, recording discrepancy risks, and limited financial transparency for residents. This research designs and implements a web-based resident administration and cash management information system using the Laravel framework, MySQL database, and WhatsApp API integration for billing notifications. The system was developed using the Software Development Life Cycle (SDLC) method with a waterfall approach and modeled using UML (Use Case Diagram, Activity Diagram, Sequence Diagram, Class Diagram). The system architecture applies Role-Based Access Control (RBAC) with four roles: RT Chairman, Secretary, Treasurer, and Resident. Black-box testing results show all ten test scenarios performed as expected. The system successfully automates the creation of financial accountability reports (LPJ), improves real-time cash transparency, and minimizes the risk of losing transaction proof documents.